2020
DOI: 10.1186/s12937-020-00557-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of green tea consumption on blood lipids: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background Strong epidemiologic evidence indicates that green tea intake is protective against hyperlipidemia; however, randomized controlled studies have presented varying results. In the present study, we aimed to conduct a literature review and meta-analysis to assess the effect of green tea on blood lipids. Methods PubMed, Embase, and the Cochrane Library were electronically explored from inception to September 2019 for all relevant studies. Random effect models were used to estimate blood lipid changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 58 publications
(57 reference statements)
4
40
0
Order By: Relevance
“…At this level, this is presumably the first evidence supporting the idea that green tea constituents may reduce the risks related to COVID-19. These results are in agreement with several lines of emerging evidence implying that green tea catechins may be effective in prevention/treatment of COVID-19 or amelioration of its severity [6][7][8][9][10]13 (as outlined in the Introduction).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…At this level, this is presumably the first evidence supporting the idea that green tea constituents may reduce the risks related to COVID-19. These results are in agreement with several lines of emerging evidence implying that green tea catechins may be effective in prevention/treatment of COVID-19 or amelioration of its severity [6][7][8][9][10]13 (as outlined in the Introduction).…”
Section: Discussionsupporting
confidence: 91%
“…7 Additionally, several factors associated with COVID-19 mortality are likely to be affected by green tea constituents. Indeed, there is evidence that green tea catechins: lower cholesterol levels; 8,9 have anti-diabetic 10 and anti-obesity effects; 11 are beneficial in cardiovascular disease 12 .…”
Section: Introductionmentioning
confidence: 99%
“…No effects were reported for green tea vs. placebo or black tea vs. placebo [ 24 ]. Xu et al found a significant decrease in total cholesterol among normal weight, overweight, and obese individuals (combined) who consumed green tea vs. placebo (weighted mean difference [WMD]: −4.66 mg/dL; 95% CI: 6.36 to −2.96; p = .0001) in a random effects meta-analysis [ 31 ]. The remaining nine older systematic reviews found no significant effects on total cholesterol across various populations [ 3 , 11 , 18 , 19 , 22 , 27 , 30 , 34 , 49 ], which may be due to a smaller number of studies and overall sample size.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that there is some fatty acid pathway that potentiates the botanical response and is suggestive for further research. The anti-inflammatory effects of the botanical extracts in attenuating inflammation was expected based on their reported effects in other species ( 11 – 16 ). However, the robust combined effects of the three extracts with ARA on some of the cytokines was novel and not to our knowledge previously reported.…”
Section: Discussionmentioning
confidence: 98%
“…In a meta-analysis of human studies it was concluded that green tea intake lowered total cholesterol and low density lipoprotein cholesterol while not influencing high density lipoprotein cholesterol. However, there was a need for greater diversity within the study population and longer duration studies ( 16 ). This study in cats tests the combination of botanical extracts to exert a beneficial effect using cytokines and selected blood parameters as response criteria.…”
Section: Introductionmentioning
confidence: 99%